2022
DOI: 10.3389/fmed.2021.805199
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Thiamine Supplementation in Patients With Septic Shock

Abstract: Septic shock is associated with unacceptably high mortality rates, mainly in developing countries. New adjunctive therapies have been explored to reduce global mortality related to sepsis. Considering that metabolic changes, mitochondrial dysfunction and increased oxidative stress are specific disorders within the path of septic shock, several micronutrients that could act in cellular homeostasis have been studied in recent decades. Thiamine, also known as vitamin B1, plays critical roles in several biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 70 publications
(111 reference statements)
0
8
0
Order By: Relevance
“…Nutritional supplementation is economical and safe and, if proven effective, can significantly reduce the burden of heart failure. Thiamine supplementation can improve the state of heart failure caused by severe thiamine deficiency, but whether thiamine supplementation is effective in critically ill patients with heart failure remains unknown ( Costa et al, 2022 ). Therefore, this study aimed to explore the correlation between thiamine use and prognosis in patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional supplementation is economical and safe and, if proven effective, can significantly reduce the burden of heart failure. Thiamine supplementation can improve the state of heart failure caused by severe thiamine deficiency, but whether thiamine supplementation is effective in critically ill patients with heart failure remains unknown ( Costa et al, 2022 ). Therefore, this study aimed to explore the correlation between thiamine use and prognosis in patients with HF.…”
Section: Discussionmentioning
confidence: 99%
“…In a study in a rat model of acute ethanol exposure, thiamine was found to increase glutathione levels and reduce liver inflammation [ 37 ]. In a study in a mouse model of sepsis, thiamine was found to reduce the production of pro-inflammatory cytokines and improve survival [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Persistent elevated lactate levels at 24-h demonstrate a strong prognostic value for in-hospital death among adult patients diagnosed with septic shock. The collective action of these mechanisms plays a role in the occurrence and/or exacerbation of thiamine deficiency in individuals diagnosed with septic shock [3].…”
Section: Thiamine Deficiency During Critical Illnessmentioning
confidence: 99%